M31 Outcomes for thoracic surgery in patients with interstitial lung disease. (December 2018) - Myall, KJ; Kamalanathan, M; Mak, SM; West, A; Agarwal, S; Lams, B
Abstract : Introduction and objectives: Outcomes for patients with interstitial lung disease (ILD) undergoing surgical lung biopsy are well described, with mortality associated with respiratory failure and acute exacerbation of ILD. 1 However, limited data exist for outcomes of thoracic surgery for other indications, particularly resection of co-existent lung cancer. Surgery may be avoided in patients with a known ILD, however, we have observed a number of cases of acute interstitial pneumonitis in patients without a pre-existing diagnosis of ILD, but in whom ILD was present on initial CT. Methods: We performed a retrospective analysis of all patients undergoing surgical resection of either a lung cancer primary or metastatecomy who were discussed at the lung cancer MDT at our site between January and July 2018. Initial CT was examined for an ILD and all surgical resections were re-examined for histological features of ILD. Results n=56 patients underwent surgery following MDT discussion. 5 (9%) had radiological evidence of an ILD, and all were UIP on histological examination. Of these patients, 1 (20%) died within 30 days of their operation, and 1 (20%) within 90 days. Both deaths were due to respiratory failure secondary to acute interstitial pneumonitis. There were no deaths within 90 days in the non-ILD group (p<0.01). 4 of 5 (80%) ILD patients required ITU admission compared with 4 of 51 (8%) non-ILD patients (p). Mean length of stay in the ILD group was 21.6 compared with 8.4 days for patients without ILD (p<0.01). Discussion: Our data highlight increased mortality, ITU admission and length of stay in patients undergoing surgical resection for lung cancer when a previously undiagnosed ILD is present on their diagnostic scan. Further work is required to understand the mechanism behind this, and potential strategies (eg. perioperative steroids) to mitigate this effect. A multidisciplinary approach is required to the treatment of these patients, especially when considering the requirement to perform surgical resection within the time constraints of the lung cancer pathway. Reference: Lettieri CJ, et al. Outcomes and safety of surgical lung biopsy for interstitial lung disease. Chest2005;127(5):1600–5.